2016
DOI: 10.1002/jaba.360
|View full text |Cite
|
Sign up to set email alerts
|

Comparing fixed‐amount and progressive‐amount DRO Schedules for tic suppression in youth with chronic tic disorders

Abstract: Chronic tic disorders (CTDs) involve motor and/or vocal tics that often cause substantial distress and impairment. Differential reinforcement of other behavior (DRO) schedules of reinforcement produce robust, but incomplete, reductions in tic frequency in youth with CTDs; however, a more robust reduction may be needed to affect durable clinical change. Standard, fixed-amount DRO schedules have not commonly yielded such reductions, so we evaluated a novel, progressive-amount DRO schedule, based on its ability t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 45 publications
0
7
0
Order By: Relevance
“…All authors responded to our inquiry. Data were available for 9 studies ( 5 , 9 , 10 , 12 , 13 , 15 , 19 , 27 , 28 ). Individual-level datasets were no longer available for older studies ( 8 , 14 , 18 , 20 , 26 ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…All authors responded to our inquiry. Data were available for 9 studies ( 5 , 9 , 10 , 12 , 13 , 15 , 19 , 27 , 28 ). Individual-level datasets were no longer available for older studies ( 8 , 14 , 18 , 20 , 26 ).…”
Section: Methodsmentioning
confidence: 99%
“…Given the central importance of voluntary tic inhibition to nonpharmacological tic management, researchers have studied various questions related to tic suppression using the Tic Suppression Task (TST) developed by Woods and Himle [( 8 ); also see ( 5 , 9 15 )]. In this paradigm, a participant is seated in front of a computer or token dispenser and told it is a “tic detector.” In reality, an experimenter unobtrusively observes the child (e.g., using a one-way mirror), and tic frequency is measured via direct observation coding.…”
Section: Introductionmentioning
confidence: 99%
“…All authors responded to our inquiry. Data were available for 9 studies [4,[9][10][11][12]14,18,26,27]. Individual-level datasets were no longer available for older studies [8,13,17,20,25].…”
Section: Study Selection a Literature Search In Databases Pubmed Andmentioning
confidence: 99%
“…Given the central importance of voluntary tic inhibition to nonpharmacological tic management, researchers have studied various questions related to tic suppression using the Tic Suppression Task (TST) developed by Woods and Himle [8] (also see [4,[9][10][11][12][13][14][15]). In this paradigm, a participant is seated in front of a computer or token dispenser and told it is a "tic detector."…”
Section: Introductionmentioning
confidence: 99%
“…Capriotti, Turkel, Johnson, Espil, and Woods (2016) suggested that further refinement of procedures used in CBIT might increase the proportion of individuals who respond to treatment. The form of assessment used during function-based intervention is one component that might benefit from further refinement (Himle et al, 2014).…”
mentioning
confidence: 99%